Nghiên cứu lý thuyết phản ứng của gốc propargyl (C3H3) và nước bằng phương pháp phiếm hàm mật độ - Hưng, Trần Hữu; Tiến, Phạm Văn; Minh Huệ, Nguyễn Thị (Vietnam Journal of Chemistry, 2015)
The reaction mechanism of the propargyl radical (C3H3*) and water (H2O) has been studied by the Density Functional Theory (DFT) using the B3LYP functional and the aug-cc-pvtz basis set. The potential energy surface (PES) for the C3H3 and H2O system was also established. Calculated results indicate that products of this reaction can be (HOCH2CCH + H), (CH≡CCH3 + OH), (CH2=CH-CHO + H), (C2H4 + HCO), (C2H5 + CO), (CH2=C=CH2 + OH), (C2H2 + CH2OH), (CHCHCHO + H2), (CHCHCHOH + H), (CH3 + CH2CO), (CH2=C=CHOH+H). However, the formation of (CH2=C=CH2 + OH) is the most favorable